DESIGN THINKING SEBAGAI METODE PERANCANGAN LOGO PERAYAAN ULANG TAHUN KOTA MAKASSAR 416 TAHUN - Rahmat Zulfikar; Ahmad Ade Nugraha; Adelia (Universitas Trisakti, 2023)
Design Thinking as The Method for Designing the Logo of Makassar City’s 416th Anniversary. A city's birthday party is a representation of enthusiasm and appeal in a series one year earlier. The general government will issue a logo as a visual element of the celebration attribute. The city's birthday celebration becomes an annual event for the city community and a space for casual communication together. The published logo will become a celebration of communication identity as well as a space for public expression. This design will aim to create an appropriate visual identity to represent expectations and as a forum for wider public expression. Design thinking is a structure of thinking and acting in producing solutions or policies. This method precipitates the process of empathy and reframing in determining the ideas produced. In the process of designing expressions and expectations are found as insights in realizing a visual identity which is then derived in the form of a logo. The visual identity of Makassar City's 416th anniversary celebration brings togetherness and innovation as a theme. This is also a message contained in communications to the public. A good visual identity can motivate people to be more participatory in urban changes in the future. Keywords: logo, visual identity, city anniversary, design thinking, Makassar city